Profil Gaya Belajar pada Mahasiswa Program Studi Bahasa Jepang - Ardipradja, Ari Rahmat Utama; Widiyani, Anggun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the learning style profile of students of the STBA YAPARI-ABA Japanese Language Studies Program in Bandung. The method used in this study is a qualitative descriptive method with observation and questionnaires as data collection instruments. The number of respondents in this study were 100 Japanese language study program students from 4 levels of study who were selected by random sampling technique. The results of this study are the mapping of student learning styles from level 1 to level 4. Although the tendency for learning styles in each dimension can be observed, there are several dimensions with respondents without a tendency showing a dominant number. When viewed from the profile of each respondent's study level, the profile combination is different. Level 1 has a learning style profile sensing - visual - reflective - sequential - introverted - inductive, level 2 has a learning style profile sensing - visual - active - global - extroverted - inductive, while levels 3 and level 4 have the same learning style profile, namely sensing – visual – reflective – global – introverted – deductive. In conclusion, from this study, the learning style profiles of students of the STBA YAPARI-ABA Bandung Japanese Language Study Program obtained a sensing – visual – reflective – global – introverted – inductive pattern. Keywords: Learning Style, Japanese Language Students, Profile